Enhanced reduction of nitrate by TDER packed with surface-modified plastic particles electrodes - Yang Zhang; Long-Wei Chu; Lei Wang; Hao-Kang Li; Qun-Fang Zhao; Yuan-Hong Ding (Ecotoxicology and Environmental Safety, 2023)
Based on Iron cathodes, nitrate could be selectively decomposed into other lower-valence nitrogen compounds, including ammonia, nitrogen gas, nitrite and nitric oxide, but the removal efficiencies of nitrate and total nitrogen (TN), are affected significantly by the synergistic effects of anodes, chloride electrolyte and conductive plastic particles electrodes. In this work, the base material Titanium (Ti) metal plates and plastic particles which surfaces were mainly coated with Ru-Sn oxidizing compounds, were applied as plates anodes and conductive particles electrodes in Three Dimensional Electrode Reactors (TDER). The Ti/RuSn plate anodes showed excellent performance on degrading nitrate, more nitrogen gas (83.84%) and less ammonia (15.51%) was produced, less TN and Iron ion (0.02 mg/L) was left in the wastewater, and less amount of chemical sludge (0.20 g/L) was produced. Furthermore, the removal efficiencies of nitrate and TN were further increased by the surface-modified plastic particles, which were cheap, reusable, corrosion-resistance, easy to obtain as manufactured materials and light to be suspended in waters. The degradation of nitrate and its intermediates was enhanced possibly by the continuous synergistic reactions initiated by hydrogen radicals, which was generated on the countless surficial active Ru-Sn sites of Ti/RuSn metal plate anodes and plastic particles electrodes, among residual nitrogen intermediates, most of ammonia was selectively converted to gaseous nitrogen by hypochlorite from chloride ion reaction.